2022
DOI: 10.1155/2022/6839634
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRA Gene Polymorphisms Are Associated with Graves’ Disease as an Autoimmune Thyroid Disease

Abstract: Background. Autoimmune thyroid disease (AITD), one of the most prevalent organ-specific autoimmune diseases, mainly includes Graves’ disease (GD) and Hashimoto’s thyroiditis (HT). This study was aimed at researching the association between AITD and single nucleotide polymorphisms (SNPs) of the HLA-DRA gene. Methods. Using Hi-SNP high-throughput sequencing technology, we detected the distribution of three SNPs (rs3177928, rs7197, and rs3129878) of HLA-DRA genotypes in 1033 AITD patients (634 GD and 399 HT ones)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Researches based genetic material have become important evidences for elucidating the pathophysiological mechanisms of diseases. Found by studies that the SNPs rs3177928 and rs7197 were correlated with AITD and GD (compared with the healthy control group), but not with HT ( 32 ). The association of the SNP CD40 C/T-1 was evaluated in patients with AITD, and a significant association for CD40 C/T-1 polymorphism with GD was found, but not with HT.…”
Section: Discussionmentioning
confidence: 99%
“…Researches based genetic material have become important evidences for elucidating the pathophysiological mechanisms of diseases. Found by studies that the SNPs rs3177928 and rs7197 were correlated with AITD and GD (compared with the healthy control group), but not with HT ( 32 ). The association of the SNP CD40 C/T-1 was evaluated in patients with AITD, and a significant association for CD40 C/T-1 polymorphism with GD was found, but not with HT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, HLA DR expression on CD33 − HLA DR + in the myeloid cell panel was most prominently associated with increased AITD risk. Notably, the expression of HLA-DR indicates T cell activation, and cells expressing HLA-DR can serve as antigen-presenting cells, playing a crucial role in CD4 + T cellmediated autoimmune thyroiditis [31,32]. CD4 + T lymphocytes can be categorized into different subsets based on cellular differentiation and phenotype, namely Th1, Th2, Th17, and regulatory T cells (Treg) [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was found that the SNPs rs3177928 and rs7197 were correlated with AITD and GBD (compared with the healthy control group), but not with HT. However, rs3177928 and rs7197 were correlated with AITD and HT in the allele model, dominant model, and overdominant model before and after gender and age adjustment, but not with HT [ 71 ].…”
Section: Genetic Factorsmentioning
confidence: 99%